THE OVERTAKING CAR SIMULATION USING THE TECHNOLOGY OF VIRTUAL REALITY - Darlis Heru Mukti; Ridho Rahman Hariadi; Anny Yuniarti; Imam Kuswardayan; Wijayanti Nurul Khotimah (Universitas Trunojoyo Madura, 2018)
Currently, motor vehicles are very widely used in everyday life. In Indonesia the growth of motor vehicle is very rapid, even reaching 10 percent per year. With the high value of the development of this motor vehicle, the number of accidents also increases. The cause of the accident is not only from the error engine but also it can be caused by the driver fault. The driver should be given more attention and information about the rule and how to ride the motor vehicles well. Sometimes the experience is needed to learn how to act in the different condition when the driver drives the motor vehicle. This paper implements the technology of Virtual Reality for the simulation of overtaking. There are two additional devices used in this research. There are the Steering Wheel and the Oculus Rift. This research aims to explore the VR technology and explore the implementation of the Steering Wheel and the Oculus Rift in overtaking simulation game.